2020
DOI: 10.1371/journal.pone.0228310
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of structure and protein of vitelline membranes of precocial (ring-necked pheasant, gray partridge) and superaltricial (cockatiel parrot, domestic pigeon) birds

Abstract: Of all the known oviparous taxa, female birds lay the most diverse types of eggs that differ in terms of shape, shell pigmentation, and shell structure. The pigmentation of the shell, the weight of the egg, and the composition of the yolk correlate with environmental conditions and the needs of the developing embryos. In this study, we analyzed the structure and protein composition of the vitelline membrane (VM) of ring-necked pheasant, gray partridge, cockatiel parrot, and domestic pigeon eggs. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…They demonstrated that the cognition of species-specific proteins that are likely to be associated with the adaptation of birds to different environmental stimuli maybe a suitable tool to replace DNA analysis. Similar conclusions were drawn by Damaziak et al 11 who analyzed the possibility of occurrence of species-specific proteins in the VM depending on their breeding and hatching specifications. It was also shown that the structure of VM differs between different bird species 11 13 .…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…They demonstrated that the cognition of species-specific proteins that are likely to be associated with the adaptation of birds to different environmental stimuli maybe a suitable tool to replace DNA analysis. Similar conclusions were drawn by Damaziak et al 11 who analyzed the possibility of occurrence of species-specific proteins in the VM depending on their breeding and hatching specifications. It was also shown that the structure of VM differs between different bird species 11 13 .…”
Section: Introductionsupporting
confidence: 83%
“…They demonstrated that the VM of chicken eggs is made exclusively of different thicknesses fibers, whereas in ducks, there are additionally strongly flattened elements called sheets. Further research using SEM and TEM allowed to find specific structures combining layers of IL and OL in the VM of emu 13 and an untypical VM formed from 9 rather than 3 layers in eggs of ring-necked pheasant and gray partridge 11 . It is unknown what are the functions of these morphological elements of the VM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations